2021
DOI: 10.1021/acs.jmedchem.1c00040
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Biased Allosteric Modulator for Cannabinoid 1 Receptor: Preclinical Anti-Glaucoma Efficacy

Abstract: We apply the magic methyl effect to improve the potency/efficacy of GAT211, the prototypic 2-phenylindole-based cannabinoid type-1 receptor (CB1R) agonist-positive allosteric modulator (ago-PAM). Introducing a methyl group at the α-position of nitro group generated two diastereomers, the greater potency and efficacy of erythro, (±)-9 vs threo, (±)-10 constitutes the first demonstration of diastereoselective CB1R-allosteric modulator interaction. Of the (±)-9 enantiomers, (−)-(S,R)-13 evidenced improved potency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 89 publications
1
15
1
Order By: Relevance
“…Co-treatment of hCB1R CHO cells with 1 μM PEA and 1 μM SR141716A-or a combination of 1 μM PEA, 1 μM Δ 9 -THC, and 1 μM SR141716A-completely prevented PEA-dependent cAMP inhibition (Figure 5). Previous reports have shown that allosteric or indirect agonism of hCB1R is blocked by SR141716A even when those allosteric ligands are not displaced in radioligand binding experiments (Garai et al, 2020, Garai et al, 2021. Therefore, the collective evidence supports PEA indirectly augmenting the activity of hCB1R in vitro.…”
Section: Confirming Hcb1r Dependence Of Peamediated Camp Inhibitionsupporting
confidence: 55%
See 1 more Smart Citation
“…Co-treatment of hCB1R CHO cells with 1 μM PEA and 1 μM SR141716A-or a combination of 1 μM PEA, 1 μM Δ 9 -THC, and 1 μM SR141716A-completely prevented PEA-dependent cAMP inhibition (Figure 5). Previous reports have shown that allosteric or indirect agonism of hCB1R is blocked by SR141716A even when those allosteric ligands are not displaced in radioligand binding experiments (Garai et al, 2020, Garai et al, 2021. Therefore, the collective evidence supports PEA indirectly augmenting the activity of hCB1R in vitro.…”
Section: Confirming Hcb1r Dependence Of Peamediated Camp Inhibitionsupporting
confidence: 55%
“…PEA has been described as a partial hCB1R agonist and bears structural similarity to the endogenous cannabinoid anandamide (AEA) (Jonsson et al, 2001;Ho et al, 2008). Therefore, PEA's activity may be consistent with allosteric agonism of hCB1R (Laprairie et al, 2019;Garai et al, 2020Garai et al, , 2021.…”
Section: Inhibition Of Forskolin-stimulated Campmentioning
confidence: 99%
“…ZCZ011 and related compounds (i.e., GAT211) show mixed allosteric agonistic and PAM properties, which have been termed CB 1 ago-PAMs (Kenakin, 2013). These compounds enhance the effects of CB 1 receptor orthosteric agonists (i.e., CP55,940, WIN55,212-2, or AEA) in a variety of functional assays, including [ 35 S] GTPγS-binding, β-arrestin recruitment and, inhibition of cAMP production, but also activate β-arrestin recruitment and inhibit cAMP production in the absence of CB 1 receptor orthosteric agonists (Ignatowska-Jankowska, Baillie, et al, 2015;Slivicki et al, 2017;Saleh et al, 2018;Tseng et al, 2019;Garai et al, 2021). Thus, additional studies (e.g., site directed mutagenesis) will be required to address the receptor mechanism(s) by which ZCZ011 ameliorates withdrawal signs in opioid-dependent mice.…”
Section: Discussionmentioning
confidence: 99%
“…2 First coined in 2009, 3 the term "magic methyl" has been used frequently since this review was published, both by an increasing number of organic chemists who develop C-H methylation strategies, [4][5][6][7][8][9][10][11] and by medicinal chemists who attribute this term to SAR trends found in their drug discovery programs. [12][13][14][15][16][17][18][19][20][21] As such, the profound effect of this small methyl group in medicinal chemistry has been discussed at length. 2,22,23 Are there other small substituents that could create a similar effect?…”
Section: Introductionmentioning
confidence: 99%